Metabolic and bioactivity insights into Brassica oleracea var. acephala - Ferreres, F. (2011)
Seeds of Brassica oleracea var. acephala (kale) were analyzed by HPLC/UV-PAD/MSn-ESI. Several phenolic acids and flavonol derivatives were identified. The seeds of this B. oleracea variety exhibited more flavonol derivatives than those of tronchuda cabbage (Brassica oleracea var. costata), also characterized in this paper. Quercetin and isorhamnetin derivatives were found only in kale seeds. Oxalic, aconitic, citric, pyruvic, malic, quinic, shikimic, and fumaric acids were the organic acids present in these matrices, malic acid being predominant in kale and citric acid in tronchuda cabbage seeds. Acetylcholinesterase (AChE) inhibitory activity was determined in aqueous extracts from both seeds. Kale leaves and butterflies, larvae, and excrements of Pieris brassicae reared on kale were also evaluated. Kale seeds were the most effective AChE inhibitor, followed by tronchuda cabbage seeds and kale leaves. With regard to P. brassicae material, excrements exhibited stronger inhibitory capacity. These results may be explained by the presence of sinapine, an analogue of acetylcholine, only in seed materials. A strong concentration-dependent antioxidant capacity against DPPH, nitric oxide, and superoxide radicals was observed for kale seeds.